Fintech and financial literacy in the Lao PDR - Peter J. Morgan; Trinh Q. Long (Asian Development Bank Institute (ADBI), 2019)
Financial literacy is gaining increasing importance as a policy objective in many countries. A growing literature has examined the role of financial literacy in an individual's income, saving behavior and the use of various financial products. However, so far, no one has examined the relationship between financial literacy and the awareness and adoption of financial technology (fintech) products, i.e., financial products provided via internet-based and mobile-based platforms. This paper examines this relationship in a developing country, the Lao People's Democratic Republic (PDR). We use information collected in the Lao PDR using the standardized questionnaire developed by the Organization for Economic Cooperation and Development International Network on Financial Education (OECD/INFE) to calculate our financial literacy. We find that a higher level of financial literacy has strong and positive effects on an individual's awareness of fintech products. This result still holds when we use a set of instrumental variables for the financial literacy variable. However, there is insufficient data to find a significant relationship between financial literacy and the use of fintech products.
Keywords: D14; G11; J26; 330; financial literacy; financial behavior; fintech; awareness of fintech; household saving; Lao PDR